Empathic Responses for Pain in Facial Muscles Are Modulated by Actor’s Attractiveness and Gender, and Perspective Taken by Observer - Jankowiak-Siuda, Kamila; Duszyk, Anna; Dopierała, Aleksandra; Bujwid, Krzysztof; Rymarczyk, Krystyna; Grabowska, Anna (Frontiers in Psychology, 2019)
Although empathy for pain is an often studied phenomenon, only few studies employing electromyography (EMG) have investigated either emotional responses to the pain of others or factors that modulate these responses. The present study investigated whether the sex and attractiveness of persons experiencing pain affected muscle activity associated with empathy for pain, the corrugator supercili (CS) and orbicularis oculli (OO) muscles, in male and female participants in two conditions: adopting a perspective of “the other” or “the self.” Fifty one participants (27 females) watched movies showing situations that included the expression of pain, with female and male and more and less attractive actors under both conditions, while the CS and OO EMG were recorded. Perspective did not affect CS muscle activity, but OO muscle activity tended to be higher in women than men under the imagine-self condition. CS muscle activity, but not OO muscle activity, was modulated by the actors’ gender and attractiveness. CS muscle activity was stronger in response to the pain of less attractive than more attractive actors, and to the pain of female actors compared to male actors. Moreover, a positive correlation was found between empathic concern, as a trait, and CS muscle activity, but only in the imagine-self condition.